Phon kānwičhai r̄ưang wichāchīpniyom kh̨̄ong khārātchakān tamrūat chan sanyābat thī tham nāthī ʻāčhān læ phūb̨̄orihān ngān nai Rōngrīan Nāir̨̄oi Tamrūat - Bančhong Suksiri, 1946- (Phāk Wichā Ratthaprasāsanasāt, Čhulālongk̨̄onmahāwitthayālai, 1992)
Study on police training and professionalism in police officer educators at Police Cadet Academy, Thailand.